2015
DOI: 10.1016/j.jcin.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

1-Year Results of the ZEPHYR Registry (Zilver PTX for the Femoral Artery and Proximal Popliteal Artery)

Abstract: The current study demonstrated 1-year real-world outcomes after drug-eluting stent treatment for FP lesions, including challenging ones in clinical practice. Lesion length, external elastic membrane area, and minimum stent area were independent predictors for restenosis. (Zilver PTX for the Femoral Artery and Proximal Popliteal Artery-Prospective Multicenter Registry [ZEPHYR]; UMIN000008433).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
128
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 139 publications
(143 citation statements)
references
References 10 publications
11
128
4
Order By: Relevance
“…Several studies revealed that the distal reference lumen/EEM CSA was useful to predict TLR after stent implantation for FP lesions 16, 18, 19) , which is consistent with our results. The results of the present study suggest that restenosis risk after EVT for long occlusive lesions with small vessel is high.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several studies revealed that the distal reference lumen/EEM CSA was useful to predict TLR after stent implantation for FP lesions 16, 18, 19) , which is consistent with our results. The results of the present study suggest that restenosis risk after EVT for long occlusive lesions with small vessel is high.…”
Section: Discussionsupporting
confidence: 92%
“…Target lesion revascularization (TLR) was defined as the need for repeated procedures (endovascular or surgical) because of a problem arising from the lesion (+1 cm proximally and distally to include edge phenomena) 6) . The definition of stent thrombosis was the same as described elsewhere 18) . The definitions of IVUS parameters followed those of a previous report 19) .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, previous studies have reported that female sex, dialysis, critical limb ischemia, disease severity, and outflow disease have been identified as independent risk factors for in-stent restenosis in femoral artery lesions rather than those chronic diseases. [2][3][4]7 Of course, several limitations (ie, small sample size) must be mentioned in terms of no positive relationship between change of cytokine levels and in-stent restenosis; the impact of baseline chronic diseases on the results of our study, 2 including in-stent restenosis, might be small.…”
mentioning
confidence: 90%
“…OFDI allows intravascular imaging with a greater scan depth and a faster pullback speed, thereby enabling the assessment of longer lesions in vessels with larger diameter, such as lesions of the femoropopliteal (FP) or carotid arteries . Especially, FP diseases exhibit considerably long stenosis or occlusion . Hence, OFDI could be a potential imaging modality for assessment of surrogate endpoints in clinical trials for FP lesions.…”
Section: Introductionmentioning
confidence: 99%